Interrelationship between inventory management and return on equity: an empirical assessment of sri lankan beverage, food and tobacco sector listed - Sritharan, V. (Journal of Business Studies, 2020)
A crucial role plays by Inventory management in balancing the cost and benefits linked with holding inventory. In the inventory management literature, several studies have been carried out regarding maintaining inventory level in a firm has been widely studied even though still there is contradiction in viewing inventory as both an asset and a liability. Few of those studies on the microeconomic determinants and consequences of inventories are somewhat inconsistent, thus this study take intention to test this issue with Beverage Food and Tobacco sector listed Companies. The methods of descriptive quantitative and Linear Regression Analysis are used in this study. The variables of inventory conversion period, operating cycle, current ratio, cash conversion cycle and return on equity are considered. Data from 2012 to 2016 was gathered as panel data from 20 firms’ annual reports of beverage food and tobacco sector for the analysis. The results expose that, operating cycle has a positive significant relationship however cash conversion cycle negatively related with dependent variable of return on equity, but other variables haven’t significant relationship with dependent variable of return on equity. In case of regression analysis result, it says inventory management has 0.158 significant impact on return on equity at 5% level as a whole model but individually operating cycle and inventory conversion period have significant impact. These findings are useful to the directors and financial management of beverage food and tobacco sector’s firms as a useful knowledge for decision makings in this field. So, this sector firms should take great care on all of these measures of inventory management when making policies and developing strategies regarding inventory management of this sector firms to improve their return on equity
Keywords: Inventory management; Return on equity; Beverage food; tobacco sector